New standardised texts for assessing reading performance in four European languages. Issue 4 (17th March 2006) - Hahn, G A; Penka, D; Gehrlich, C; Messias, A; Weismann, M; Hyvärinen, L; Leinonen, M; Feely, M; Rubin, G; Dauxerre, C; Vital-Durand, F; Featherston, S; et al.
Abstract : Aims: To develop standardised texts for assessing reading speed during repeated measurements and across languages for normal subjects and low vision patients. Methods: 10 texts were designed by linguistic experts in English, Finnish, French, and German. The texts were at the level of a sixth grade reading material (reading ages 10–12 years) and were matched for length (830 (plus or minus 2) characters) and syntactic complexity, according to the syntactic prediction locality theory of Gibson. 100 normally sighted native speaking volunteers aged 18–35 years (25 per language) read each text aloud in randomised order. The newly designed text battery was then applied to test the reading performance of 100 normally sighted native speaking volunteers aged 60–85 years (25 per language). Results: Reading speed was not significantly different with at least seven texts in all four languages. The maximum reading speed difference between texts, in the same language was 6.8% (Finnish). Average reading speeds (SD) in characters per minute are, for the young observer group: English 1234 (147), Finnish 1263 (142), French 1214 (152), German 1126 (105). The group of older readers showed statistically significant lower average reading speeds: English 951 (97), Finnish 1014 (179), French 1131 (160), German 934 (117). Conclusion: The authors have developed a set of standardised, homogeneous, and comparable texts in four European languages (English, Finnish, French, German). These texts will be a valuable tool for measuring reading speed in international studies in the field of reading and low vision research.